STUDENTS’ MOTIVATION IN LEARNING ENGLISH - Zuniarti, Nemi; Salam, Urai; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstrak: Penelitian ini bertujuan untuk mengetahui jenis motivasi siswa yang paling dominan dan tingkat motivasi siswa dalam belajar bahasa inggris. Partisipan dalam penelitian ini berjumlah 34 siswa. Data penelitian diperoleh dari kuesioner dan interview. Hasil penelitian menunjukkan bahwa 91.2% motivasi siswa dalam belajar bahasa inggris masuk dalam kategori cukup baik. Dari hasil kuesioner ditemukan 58.8% memiliki motivasi intrinsik to experience dalam belajar bahasa inggris. Hal ini diperkuat oleh hasil inteview bahwa alasan siswa belajar bahasa inggris karena bahasa inggris sebagai bahasa internasional sangat penting untuk dipelajari dan dikuasai. Walaupun mereka memiliki hambatan ketika mempelajarinya, mereka tetap memiliki keinginan untuk mempelajarinya. Kata Kunci : Motivasi siswa, Belajar bahasa inggris. Abstract: This is a descriptive-survey research of third grade students of SMP Negeri 2 Pontianak in academic year 2014/2015. It was conducted to figure out the type of motivation that students mostly have and the level of students’ motivation in learning English. In this study, there were 34 students participating in ths research. The data were derived from questionnaire and interview. The data showed that 91.2% of the students’ motivation in learning English mostly was qualified in average to good level. From the questionnaire, it was found out that 58.8% of the students had intrinsic motivation to experience as their motivation in learning English. In addition, the interview showed that students learned english because they thought Englsih as an international language, English is important to be learnt and mastered. Even though they had obstacles while learning, they had motivation to learn English. Keywords : Students’ motivation, Learning English.